A novel anxiety-associated SNP identified in LYNX2 (LYPD1) is associated with decreased protein binding to nicotinic acetylcholine receptors - Anderson, Kristin R.; Cao, Wenpeng; Lee, Hui Sun; Crenshaw, Mark A.; Palumbo, Talulla B.; Fisher-Perez, Ethan; DeGraaf, Amanda; Rogu, Peter; Beatty, Maria A.; Gracias, Gabrielle M.; Pisapati, Avani V.; Hoffman, Katie; et al. (Frontiers in Behavioral Neuroscience, 2024)
Introduction Anxiety disorders are among the most common mental illnesses in the US. An estimated 31.1% of U.S. adults experience any anxiety disorder at some time in their lives. Understanding some of the molecular underpinnings of anxiety could lead to improved treatments over current strategies focusing on symptom relief rather than root causes. One significant neurotransmitter system exerting control over anxiety is the nicotinic receptor subdivision of the cholinergic system. The murine Lynx2 gene, encoding a protein modulator of nicotinic acetylcholine receptors, is expressed in anxiety-related neural circuitry in rodents and has been functionally associated with anxiety-like behavior. Methods We examined variations in the human LYNX2 (LYPD1) gene and their potential effects on anxiety levels in a cohort of 624 participants. Participants completed validated anxiety questionnaires (e.g., STICSA and STAI), which assessed both their current anxiety and their general tendency to experience anxiety. Possible functional alterations due to one such mutation was assessed through atomic force microscopy (AFM) and computational modeling. Results We identified a previously unreported single nucleotide polymorphism (SNP) in the mature protein-coding region of LYNX2 that was associated with significantly higher than normal anxiety scores. These elevated scores resembled those seen in patients clinically diagnosed with generalized anxiety disorder and panic disorder, although this genetically defined subpopulation did not typically report such diagnoses. Through computational modeling of the homopentameric α7 nicotinic receptor subtype and in vitro atomic force microscopy (AFM), we discovered that a specific LYNX2 SNP is linked to a reduced binding affinity between the LYNX2 protein and nAChRs, offering a potential functional explanation for the role that this mutation may play in anxiety. Discussion A polymorphism in LYNX2, which codes for an inhibitory modulator of nicotinic acetylcholine receptors, has the potential to lead to sensitized nicotinic receptor activity in anxiety-related circuits. The LYNX2 protein has been shown to bind to multiple nicotinic acetylcholine receptor subtypes, including α4β2, α7, and α3β4 subtypes, each of which have been shown to be involved in affective behaviors. This work suggests that a subpopulation of individuals harboring a deleterious mutation in LYNX2 may predispose them to anxiety through abnormal nicotinic receptor control. In the future, this work may lead to the development of a biomarker for anxiety or a diagnostic tool for the early detection of individuals with susceptibility to anxiety.